An Empirical Investigation of the Disaggregated Import Demand Function: Non-linear ARDL Framework. Issue 2 (May 2021) - Kathuria, Khyati; Kumar, Nand
The article estimates the disaggregated import demand function for India using annual time series data for the period 1995–2017. The empirical results reveal strong evidence of long-run stable relationship among the variables considered in the study. The disaggregated import demand function is estimated for India using linear and non-linear ARDL model. The estimated linear ARDL model shows that gross capital formation, exports and relative prices affect import demand positively and significantly, both in the short and long run. While the impact of final consumption expenditure was found to be insignificant in the short run, it affects import demand significantly and positively in the long run. On the other hand, the result of the non-linear ARDL model shows the evidence of asymmetry in the impact of relative prices (positive and negative changes) on import demand, both in the short and long run. JEL Codes: F41, B17, B41, C51